Dificultades de aprendizaje y el rendimiento escolar en la asignatura de ciencias naturales de octavo, noveno y décimos años de educación general básica de la unidad educativa Vicente Anda Aguirre, sección diurna La Dolorosa, durante el año lectivo 2010 - 2011. Propuesta alternativa - Correa Carreño, Ramiro Alejandro (2014)
This study was conducted in the Canton Loja capital of the province of Loja, with students of Eighth, Ninth and say years of Basic General Education School "La Dolorosa" during the school year between the first and second quarter the year 2010 to 2011. The research question is: What is the impact of learning difficulties in school performance in the subject of Natural Sciences of the eighth, ninth and tenth years of General Basic Education Educational Unit "Anda Vicente Aguirre" daytime section "La Dolorosa" during the school year 2010- 2011 ?, generating research objective: to analyze how learning disabilities affect academic performance in the subject of Natural Sciences Eighth, Ninth and say years of Basic Education General Education Unit Anda Vicente Aguirre , the Sorrowful section daytime during the school year 2010 - 2011 The research is exploratory and descriptive. For information processing of text, and Deductive Method was used for the collection and analysis of field data, the Inductive Method will be used as a tool for analysis from a particular perspective generalize results. To fulfill the objectives of the observation techniques and the Survey, mainly be used. Research techniques were supported by test, index cards, tokens and field data collection instruments and tabulation. There were three types of surveys: one aimed at students, teachers and parents. The total universe was represented by ninety-two teachers and 1072 students, of which 482 belong to the basic general education, and there are 7 teachers CCNN To calculate the sample 72 students, a percentage that corresponds to 15% of the total universe, which students following results were reached: The techniques of learning most used in the process of learning of NPPs are: reading comprehension, group work and the use of graphic organizers, but the mechanical memory, verbalista type is used and oriented learning concepts rather than processes. Little use of ICT as a form of evidence really supports teaching; and laboratory practices CCNN They are biased. Pedagogical recovery aims to improve the skills and not the skills development with performance criterion, indicating that teachers NPP Recovery processes focus only on improving averages and not the process development and the acquisition of skills with performance criterion. It is recommended to explore the fact that the teaching styles of teachers not engage the learning styles of students, which negatively influences the development of the SAP and channel a study to determine the reasons why not apply ICT in the learning of NPPs